2006
DOI: 10.2337/db05-1584
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hypothalamic KiSS-1 System and Rescue of Defective Gonadotropic Responses by Kisspeptin in Streptozotocin-Induced Diabetic Male Rats

Abstract: Hypogonadotropism is a common feature of uncontrolled diabetes, for which the ultimate mechanism remains to be elucidated. Kisspeptins, ligands of G protein-coupled receptor 54 (GPR54) encoded by the KiSS-1 gene, have recently emerged as major gatekeepers of the gonadotropic axis. Alteration in the hypothalamic KiSS-1 system has been reported in adverse metabolic conditions linked to suppressed gonadotropins, such as undernutrition. However, its potential contribution to defective gonadotropin secretion in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
177
3
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 222 publications
(197 citation statements)
references
References 45 publications
13
177
3
4
Order By: Relevance
“…Not only can central injections of kisspeptin reverse the fasting-induced inhibition of GnRH secretion, but kisspeptin administration has also been shown to rescue the GnRH decline in rats that are treated with leptin antibodies (Castellano et al, 2006). These findings suggest that kisspeptin is involved in relaying metabolic signals to the neuroendocrine reproductive axis.…”
Section: Kisspeptinmentioning
confidence: 92%
See 1 more Smart Citation
“…Not only can central injections of kisspeptin reverse the fasting-induced inhibition of GnRH secretion, but kisspeptin administration has also been shown to rescue the GnRH decline in rats that are treated with leptin antibodies (Castellano et al, 2006). These findings suggest that kisspeptin is involved in relaying metabolic signals to the neuroendocrine reproductive axis.…”
Section: Kisspeptinmentioning
confidence: 92%
“…Kisspeptin also interacts with the insulin signaling pathway in the hypothalamus. Rats that are rendered diabetic, thus having systemic glucose insufficiency, have diminished expression of Kiss1 mRNA, which can be reversed with insulin therapy (Castellano et al, 2006). Thus, together with galanin-like peptide (GALP), pro-opiomelanocortin (POMC) and NPY neurons, Kiss1 neurons are likely to serve as cellular conduits for relaying information about circulating levels of leptin and insulin to the neuroendocrine reproductive axis.…”
Section: Kisspeptinmentioning
confidence: 99%
“…In recent years, the metabolic regulation of the hypothalamic KISS1 system has been exposed, mainly by experimental studies in rodents, where conditions of negative energy balance were shown to induce variable degrees of inhibition of Kiss1 mRNA expression [34,[40][41][42][43]. These analyses, together with the rescue of gonadotropic function by exogenous kisspeptin in these conditions, have allowed us to suggest that kisspeptin neurons at the hypothalamus operate as sensor and neuroendocrine conduit for conveying metabolic information onto brain reproductive centers (likely, GnRH neurons), thereby contributing to the well-known coupling between body energy status, puberty onset and fertility [42,44].…”
Section: Molecular Mechanisms For the Metabolic Regulation Of Hypothamentioning
confidence: 99%
“…Compelling evidence, though, has demonstrated that the adipose hormone, leptin, is a master hormonal regulator of hypothalamic Kiss1, as evidenced by rodent studies, where conditions of hypoleptinemia were linked to decreased hypothalamic expression of Kiss1 mRNA, which could be rescued by central administration of leptin [41,45]. However, some crucial facets of this regulatory pathway remain to be unfolded.…”
Section: Molecular Mechanisms For the Metabolic Regulation Of Hypothamentioning
confidence: 99%
“…fasting) or signals of energy availability (e.g. leptin; Castellano et al 2005Castellano et al , 2006bSmith et al 2006;Luque et al 2007). Recent evidence suggests that GnIH may interact with the ingestive system in chickens and rats, with injections of GnIH leading to a significant increase in feeding behaviour (Tachibana et al 2005;Johnson et al 2007).…”
Section: Future Directionsmentioning
confidence: 99%